2006
DOI: 10.1536/ihj.47.67
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Segmental Artery Ratio An Alternative to the Pulmonary Artery Index in Patients With Tetralogy of Fallot

Abstract: SUMMARYThe objective of this study was to determine a reliable, alternative ratio to the pulmonary artery (PA) index, which will help to estimate the adequacy of postoperative pulmonary blood flow in patients with tetralogy of Fallot.We propose the pulmonary segmental artery ratio (PSAR), which is an angiographic measure for the quantitative standardization of the total number of pulmonary segmental arteries in a patient. The expected value of the PSAR is 1 and it is constant after the 16 th week of intrauteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…It is characterized by a membranous or fibromembranous tissue that partly or fully surrounds the subaortic region. This membranous shelf causing flow turbulence in the LVOT can result in progressive subaortic stenosis, concentric left ventricular hypertrophy, and secondary aortic regurgitation [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by a membranous or fibromembranous tissue that partly or fully surrounds the subaortic region. This membranous shelf causing flow turbulence in the LVOT can result in progressive subaortic stenosis, concentric left ventricular hypertrophy, and secondary aortic regurgitation [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Mean PAP values of 30 mm Hg or less were selected for VSD closure at a reasonable postoperative right ventricular pressure [7]. Recently, Honjo and associates [8] demonstrated that the functional intraoperative flow study is highly correlated with postoperative hemodynamics, and more accurately predicts successful VSD closure than anatomic indices [9][10][11][12]. In addition, Zhu and colleagues [13] explored the flow study accuracy as a predictor of medium term survival after unifocalization, concluding that pressures of 25 mm Hg or greater are associated with an increased hazard of death (hazard ratio 9.8, 95% confidence interval: 1.14 to 83.30).…”
mentioning
confidence: 99%
“…ACG has been performed to evaluate the PA; and, indeed, a recent study still used ACG to measure PA size. 20 As we noted above, ACG is an invasive technique that cannot be used frequently, and 16-MDCT is less invasive. For follow-up of the PA size, we suggest use of MDCT as well as MRA.…”
Section: Discussionmentioning
confidence: 97%